Styrax carranzae, a new name for extant Styrax lanceolatus P.W. Fritsch non Engelhardt (Styracaceae) - Doweld, Alexander B. (Phytotaxa, 2020)
In revising fossil records of the genus Styrax Linnaeus (1753: 444) for the International Fossil Plant Names Index (IFPNI, 2014 onwards) with the aim of listing all fossil plant species (Doweld 2015, 2016a), it became apparent that a few fossil-species are later illegitimate homonyms of the extant species of Styrax, and their nomenclature was recently resolved by proposing new replacement names for them (Doweld 2016b). However, an additional case of the homonymy of an extant species by a preoccupied name in fossils remained unsettled.